Implementasi Peraturan Komisi Pemilihan Umum Tentang Kampanye Pemilihan Umum Tahun 2019 di Kabupaten Gianyar - Sri Sulandari; I Wayan Astawa; Luh Riniti Rahayu; Putu Surya Wedra Lesmana (Program Studi Administrasi Negara, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Warmadewa, 2021)
One of the stages of the 2019 election is the implementation of the election campaign in which the General Election Commission has issued PKPU Number 23 concerning the 2019 General Election Campaign as a legal basis for the implementation of the election campaign in Indonesia. The objectives and benefits of the research refer to the formulation of the problem. The research method that the writer uses is descriptive qualitative. Research shows that the implementation of the General Election Commission’s regulations regarding the 2019 General Election Campaign in Gianyar Regency is generally going well, this is evidenced by the implementation of the 2019 election campaign stages have followed provisions and regulations that have been established, and election organizers can both facilitating election participants in accordance with what is mandated by the general election commission regulations regarding the 2019 election campaign. There are several factors inhibiting the implementation of the general election commission regulations regarding the 2019 election campaign, including the size factor and policy objectives, the human resource factor possessed by the election organizers. and election participants, the characteristic factors of the executing agent, the attitudes or tendencies of the implementers, the inter-organizational communication factors and the activities of the executors, and finally the economic, social, and political environmental factors that exist in Gianyar District.